Risk factors found associated with hypertension in adults males and females (40-60 years) in district Abbottabad (NWFP)-Pakistan - Khattak, Muhammad Muzaffar Ali Khan; Raiz, Saima; Khan, Alam (2007)
Objective: This study was conducted in the District Abbottabad, North West Frontier Province (NWFP)-Pakistan. The objective of this study was to study the association of the risk factors with the hypertension in this part of the world. Methods: Two hundred respondents of both sexes (100 Male & 100 Female) with an age range of 40-60 years were included from the different locations of the area under study. Fifty percent respondents of both the sexes were either normotensive or hypertensive. Results: The hypertensive cases were established cases of high blood pressure. Prior, the study protocol, all the respondents were explained in detail about the study and upon willingness included in this study. Personal information i.e. age, sex, body weight & heights and income level were recorded on the day of the registration. Furthermore, the respondents were given food frequency questionnaires on the day of the registration for later collection. These questionnaires were later collected. The food frequencies and any possible association with hypertension were determined from the questionnaires data.The compiled data was analysed by using a statistical package MINITAB (release 8.2) Inc. State. Drive. USA. The mean age of the male & female respondents was 49.2 5.0 and 47.0 6.0 years respectively whereas the mean BMI of the male & female respondents was 24.0 3.0 5.0 and 27.0 5.0 respectively. Among the male subjects 7, 54, 38 & 1 % were under weight, normal weight, overweight and obese respectively. Similarly, in female 2, 35, 42 & 21 % were under weight, normal weight, overweight and obese respectively. The frequency of over-weight and obesity was higher in male and female hypertensive subjects. The obesity in male was 2 & 40 % in male and female respectively. The family history of hypertension, diabetes & heart related problem was 35%-39%, 5%-10%, 8%-15% in male and females respectively. Age, family history of blood pressure, heart related problems and smoking were significantly positively correlated being the r values 0.322, 0.270 0.213 and 0.337respectively. The higher frequency of foods appeared to be significantly correlated with hypertension are cream (balai), parata, meat, biscuits, cakes & pakoras being the r values 0.147, 0.206, 0.157, 0.168, 0.175 and 0.177 respectively. The physical activity of the respondents was significantly (r = -0.375; P<0.0001) negatively correlated with hypertension. The food sources having higher frequencies during the month and were negative correlated with hypertension are fruit, vegetable, vegetable soup, whole bread and kitchri being the r value -0.310, -0.198, -0.231, -0.168 & -0.151 respectively. Conclusions: The correlation analysis suggests that the conventional risk factors are not different in this particular study. Similarly, the food sources like cream (balai), parata, meat, biscuits, cake, and pakora are positively associated with hypertension whereas whole bread, fruit, vegetables, kitchri and vegetable soup are negatively associated with hypertension.